Laser sintering with plastics : technology, processes, and materials - Schmid, Manfred, 1958- (Hanser Publications ; Hanser Publishers, 2018)
"Laser Sintering (LS) with plastics is one of the most promising additive manufacturing technologies: it is currently regarded as the process most likely in the future to permanently cross the border between prototyping and the production of functional parts. This step is challenging because it means that the technology must meet certain requirements that are also valid for traditional and established production processes. Only by succeeding at this step can a wide industry acceptance of LS be expected in the future. In this context, this book covers all levels of the LS process chain, including: - Current state of the machine technology - Essential process steps, both before and during sintering - Specific demands of the materials, powder production methods, and evaluation of powder properties - Mechanical properties and density of the parts produced by LS Examples of LS-produced parts are given, including those with special design features, to illustrate the characteristics and also the limitations of the LS method. In particular, the distinct advantages of LS parts over parts produced with other plastics processing methods (e.g., injection molding) are discussed."--Resumé vydavatele
Přeloženo z německého originálu Selektives Lasersintern (SLS) mit Kunststoffen
Na obálce uvedeno celé jméno autora: Manfred Schmid
Keywords: slinování; laserová technika; zpracování plastů; polymerní materiály; výrobní technologie; materiálové technologie; sintering; laser technology; plastics processing; polymer materials; manufacturing technology; material technologies; monografie; monographs